2019
DOI: 10.1073/pnas.1820601116
|View full text |Cite
|
Sign up to set email alerts
|

Biomass losses resulting from insect and disease invasions in US forests

Abstract: Worldwide, forests are increasingly affected by nonnative insects and diseases, some of which cause substantial tree mortality. Forests in the United States have been invaded by a particularly large number (>450) of tree-feeding pest species. While information exists about the ecological impacts of certain pests, region-wide assessments of the composite ecosystem impacts of all species are limited. Here we analyze 92,978 forest plots distributed across the conterminous United States to estimate biomass loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 31 publications
1
103
0
Order By: Relevance
“…In particular, the number of non-native insects has grown exponentially since the 1950s (Seebens et al, 2017), making them the most numerous and costly group of invasive animals worldwide (Bradshaw et al, 2016;Fei, Morin, Oswalt, & Liebhold, 2019).…”
mentioning
confidence: 99%
“…In particular, the number of non-native insects has grown exponentially since the 1950s (Seebens et al, 2017), making them the most numerous and costly group of invasive animals worldwide (Bradshaw et al, 2016;Fei, Morin, Oswalt, & Liebhold, 2019).…”
mentioning
confidence: 99%
“…Beech bark disease was prevalent at all three sites and probably caused some tree mortality at each site but it is unlikely it was responsible for the 20 and 60% increases in cumulative beech mortality we observed at Oakfield in 2018 and Sandy Lake in 2015, respectively. Annual mortality from beech bark disease is greatest during the first 10 years of invasion (the "killing front") and subsequently averages only about 2% of live biomass in the aftermath forest (Fei et al, 2019); diseased beech that survive the initial wave of mortality survive for many years (Gavin and Peart, 1993;Morin et al, 2007). Contrary to our prediction, our contingency table analysis showed that beech mortality was independent of the degree of cankering by beech bark disease, except at Mount Uniacke, where infestation by the weevil was relatively low until 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The insect likely became established in North America in the early 1990s, began killing trees by 1997 (Siegert, McCullough, Liebhold, & Telewski, 2014), and has since killed millions of Fraxinus spp. in the eastern USA (Herms & McCullough, 2014; Morin, Liebhold, Pugh, & Crocker, 2017), resulting in significant biomass losses (Fei, Morin, Oswalt, & Liebhold, 2019). Initial radial range expansion by EAB at the sub‐county level occurred at ~4 km/year between 1998 and 2001, and ~13 km/year between 2001 and 2003 (Siegert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%